2002
DOI: 10.1002/1522-2675(200208)85:8<2523::aid-hlca2523>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects by Antioxidants on the Oscillations of the Briggs-Rauscher Reaction in Mixed EtOH/H2O Medium

Abstract: The Briggs-Rauscher (BR) oscillating reaction in mixed 20% EtOH/H 2 O (v/v) medium is studied together with the inhibitory effects by the addition of hydroalcoholic solutions of antioxidants on its oscillatory regime. As in aqueous BR mixtures, the inhibitory effect consists of an immediate cessation of oscillations, an inhibitory time that linearly depends on the concentration of the antioxidant added, and subsequent regeneration of oscillations. The effects of several water-insoluble and water-soluble antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…For this topic, there is a dearth in the literature. In fact, there is only one paper that deals with a hydroalcoholic medium to test the antioxidant activity of water-insoluble antioxidants; it was found that the mechanism was the same in either aqueous or mixed medium (Cervellati et al 2002). Early scouts indicated that the olive oil has to be dissolved in a suitable solvent to give reproducible inhibition times: emulsions of EVOO samples with ethanol or isopropylic alcohol were ruled out because the inhibition time of the perfectly shaken emulsion changed as the emulsion was settling down.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…For this topic, there is a dearth in the literature. In fact, there is only one paper that deals with a hydroalcoholic medium to test the antioxidant activity of water-insoluble antioxidants; it was found that the mechanism was the same in either aqueous or mixed medium (Cervellati et al 2002). Early scouts indicated that the olive oil has to be dissolved in a suitable solvent to give reproducible inhibition times: emulsions of EVOO samples with ethanol or isopropylic alcohol were ruled out because the inhibition time of the perfectly shaken emulsion changed as the emulsion was settling down.…”
Section: Resultsmentioning
confidence: 66%
“…Compared to other methods, the BR assay has many advantages: it is easy, inexpensive and rapid, and has often been successfully used to test the antioxidant activity (Cervellati et al 2002;Höner and Cervellati 2003;Prenesti et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…involves many reactions working together. [16][17][18][19][20] The reaction can follow both a radical and a non-radical path, according to the low or high iodide concentration. Each reaction path creates the conditions that favor the alternative path, hence the concentration of iodide and the reaction electrochemical potential oscillate.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other methods, the BR assay has not only theoretical advantages but also many practical advantages: it is easy, inexpensive and rapid and has often been successfully used to test the antioxidant activity. [15][16][17][18] To standardize the antioxidant capacity of a sample a standard antioxidant molecule must be used. We already successfully tested gallic acid as reference compound: the equation parameters of the straight line optimized for gallic acid at 20.0 C are t in ¼ 5890GA + 13.9, R ¼ 0.9973, where GA represents the mass of gallic acid added to the BR mixture (ranging from 0.02 to 0.04 mg).…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2, the concentration of vitamin E in the mixture has to be at mm level in order to obtain reasonable inhibition times, while for hydrophilic antioxidants in the malonic acid-based BR oscillator, very high inhibition times were obtained at mm level [2 -5] 4 ).…”
Section: Results -Behavior Of the Completely Unperturbed And Perturbmentioning
confidence: 99%